ATR inhibition broadly sensitizes ovarian cancer cells to chemotherapy independent of BRCA status - Huntoon, Catherine J. (2013)
Replication stress and DNA damage activate the ATR-CHK1 checkpoint signaling pathway that licenses repair and cell survival processes. In this study, we examined the respective roles of the ATR and CHK1 kinases in ovarian cancer cells using genetic and pharmacological inhibitors of in combination with cisplatin, topotecan, gemcitabine and the poly(ADP-ribose)-polymerase (PARP) inhibitor veliparib (ABT-888), four agents with clinical activity in ovarian cancer. RNAi-mediated depletion or inhibition of ATR sensitized ovarian cancer cells to all four agents. In contrast, while cisplatin, topotecan and gemcitabine each activated CHK1, RNAi-mediated depletion or inhibition of this kinase in cells sensitized them only to gemcitabine. Unexpectedly, we found that neither the ATR kinase inhibitor VE-821 or the CHK1 inhibitor MK-8776 blocked ATR-mediated CHK1 phosphorylation or autophosphorylation, two commonly used readouts for inhibition of the ATR-CHK1 pathway. Instead, their ability to sensitize cells correlated with enhanced CDC25A levels. Additionally, we also found that VE-821 could further sensitize BRCA1-depleted cells to cisplatin, topotecan and veliparib beyond the potent sensitization already caused by their deficiency in homologous recombination. Taken together, our results established that ATR and CHK1 inhibitors differentially sensitize ovarian cancer cells to commonly used chemotherapy agents, and that CHK1 phosphorylation status may not offer a reliable marker for inhibition of the ATR-CHK1 pathway. A key implication of our work is the clinical rationale it provides to evaluate ATR inhibitors in combination with PARP inhibitors in BRCA1/2-deficient cells.